Answers

2016-03-03T09:31:50+05:30
Formula:
tn=a+(n-1)d
t7=> a+(7-1)=1/9
         a+6d = 1/9      ____I equation
t9 => a + 8d = 1/7  _____ II equation
on solving equation I & II
equ I  - equ II
   (6-8)d = 1/9 - 1/7
     -2d   = -2/63
         d = 1/63    _____Sub in equ I
a + 6d =1/9
a + 6/63 = 1/9
  a =  1/9 - 6/63
    a = 1/63
therefore, t63 = a + 62 d
                        = 1/63 + 62/63
                          = 63/63
                 t63 = 1


1 5 1
if you satisfied with this answer pls. mark its has brainliest